Exploring the potential association between dietary factors and autism spectrum disorder: a Mendelian randomization analysis and retrospective study - Guo, Yan-Shuo; Wang, Yu; Zhu, Meng-Na; Che, Chao; Yu, Xiao-Xiao; Cai, Zhi-Feng; Leng, Juan; Chen, Kun-Ping; Cao, Ai-Hua (Frontiers in Nutrition, 2026)
BackgroundAutism spectrum disorder (ASD) is a neurodevelopmental condition involving complex genetic and environmental interactions. This study aimed to investigate the causal relationships between dietary factors, ketones, food allergy, and the risk of ASD using Mendelian randomization (MR) and clinical research.MethodsWe used two-sample MR to analyze the causal associations between 199 dietary factors, ketones, food allergy, and ASD risk using genome-wide association study (GWAS) data. Validity was assessed using sensitivity analyses. Additionally, a retrospective study (n = 78, age range 2–7 years) evaluated the clinical effects of a gluten-free casein-free (GFCF) diet on ASD symptoms, as measured by the Childhood Autism Rating Scale (CARS) and the Autism Diagnostic Observation Schedule, Second Edition (ADOS-2).ResultsMR analysis identified significant positive causal effects on ASD risk for wholemeal pasta (OR: 16.0, 95% CI 2.86–89.4, p = 0.002) and cheese spread (OR: 9.53, 95% CI 1.64–55.4, p = 0.020). It is crucial to emphasize that these estimates represent the lifetime effect of a genetic predisposition to a higher intake level, not the risk from short-term consumption. The very wide confidence intervals indicate substantial uncertainty in the point estimates. Banana had a protective effect (OR: 0.50, 95% CI: 0.30–0.83, p = 0.008). No causal links were identified for the other factors. Mediation analysis suggested that cheese spread intake increased ASD risk partly by lowering HLA-DR + T cell CD45 levels (10.2% mediation) and increasing anti-Epstein–Barr virus IgG seropositivity (12.9% mediation). Clinically, Although the GFCF diet did not significantly improve ADOS-2 and CARS scores, it showed greater improvement compared to the normal diet group. This diet significantly reduced milk- and wheat-specific IgG levels, indicating its ability to effectively modulate immune responses.ConclusionThis study provides genetic evidence of causal relationships between specific dietary factors and ASD risk. Clinical data indicate that adhering to a gluten-free, casein-free diet and avoiding related allergenic foods can effectively modulate food-specific immune responses and may also improve ASD symptoms. These findings contribute to deepening our understanding of ASD etiology and optimizing nutritional treatment protocols.